The Application of Mopsi Module for Breast Cancer Patients - Musa, Norhafizah; Yaakub, Azahar; Ihwani, Siti Suhaila; Muhtar, Adibah; Abdullah, Abdul Hafiz (International Journal of Psychosocial Rehabilitation, 2020)
Pressure or stress is a common occurrence or experience in every individual's life, especially to those that are afflicted with an illness, However, what distinguishes it is the patient's perception of the pressure itself. There are numerous events or situations that occur in life that trigger the existence of stress on the patient. These trigger factors arise in many forms such as physical, behavioral, social, emotional, and their own thoughts. The effect of stress on the patient is related to the attitude, character and the perception derived from the pressure. This article intends to identify stress changes in breast cancer patients after the apllication of MOPSI module. This study was carried out on two breast cancer patients using a detailed interview method and observation. Data was analysed using Nvivo11 and triangulation. The findings show that patients that consistently applied MOPSI experienced positive physical, psychological and social changes. The application of the MOPSI module significantly changes daily routines to become healthier and reduces the pressure or stress experienced.